KEY PERFORMANCE INDICATOR DALAM MENGUKUR KINERJA KARYAWAN DI UNIT PENGELOLA KEGIATAN LESTARI - Syafrudin .; Diana Djuwita; Sri Mulyati (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2017)
Abstract Activity Management Unit Lestari established by the inter-village meetings which choose the evaluation process by using Key Performance Indicator. As a financial institution is very sensitive so it is necessary to determine the application of performance evaluation in evaluating an employee's performance required tools or methods are precisely tailored to the institution so that performance can be measured objectively. This study used a qualitative approach is to perform observations, interviews and review documents on Activity Management Unit Lestari. Primary data in this study is data obtained directly from the information through interviews and the results obtained from interviewing employees Activity Management Unit Lestari is then performed data reduction, data presentation and then verification and confirmation data. Results Overall Performance Assessment Activity Management Unit sustainable way based on scoring criteria with the Key Performance Indicator can be seen overall performance enough, from a financial perspective is not good, from the customer perspective is good, from the perspective of internal business processes poorly and growth perspective and learning both accumulated got enough.  Keywords: Performance Measurement, Key Performance Indicator, Employee Performance. Abstrak Unit Pengelola Kegiatan Lestari dibentuk oleh musyawarah antar desa yang memilih proses evaluasi dengan menggunakan Key Performance Indicator. Sebagai lembaga keuangan sangatlah sensitive maka dalam mengevaluasi sebuah kinerja karyawan diperlukan alat atau metode yang tepat disesuaikan dengan lembaga sehingga kinerja dapat diukur secara objektif. Penelitian ini menggunakan pendekatan kualitatif yaitu dengan melakukan pengamatan, wawancara dan penelaahan dokumen pada Unit Pengelola Kegiatan Lestari. Hasil Keseluruhan Penilaian Kinerja Unit Pengelola Kegiatan Lestari berdasarkan Kriteria penilaian dengan Key Performance Indicator dapat diketahui kinerja secara keseluruhan cukup, dari perspektif keuangan kurang baik, dari perspektif pelanggan baik, dari perspektif proses bisnis internal kurang baik dan perspektif pertumbuhan dan pembelajaran baik diakumulasi mendapat nilai cukup. Kata Kunci: Pengukuran Kinerja, Key Performance Indicator, Kinerja Karyawan.